2022
DOI: 10.1039/d2lc00513a
|View full text |Cite
|
Sign up to set email alerts
|

Motor-like microlasers functioning in biological fluids

Abstract: Microlasers integrated with biological systems have received tremendous attention for their intense light intensity and narrow linewidth recently, serving as a powerful tool for studying complex dynamics and interactions in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Recently reported LC sensor based on the whispering gallery mode (WGM) due to the simple structure, high quality factor, and small mode volume of WGM optical microcavities have been widely used in a variety of fields. [15][16][17][18] On the basis of naked eye observation utilising POM, the optofluidic sensor is implemented by integrating the POM with the WGM laser spectroscopy, resulting in a more sensitive and precise characterisation. [19][20][21][22][23] In this work, we presented a biosensing platform based on the LC-amplified optofluidic WGM resonator, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently reported LC sensor based on the whispering gallery mode (WGM) due to the simple structure, high quality factor, and small mode volume of WGM optical microcavities have been widely used in a variety of fields. [15][16][17][18] On the basis of naked eye observation utilising POM, the optofluidic sensor is implemented by integrating the POM with the WGM laser spectroscopy, resulting in a more sensitive and precise characterisation. [19][20][21][22][23] In this work, we presented a biosensing platform based on the LC-amplified optofluidic WGM resonator, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, micro/nanomotors have emerged as active agents for biosensing owing to their unique ability to propel and travel in biofluids. By converting energy from the surrounding environment into autonomous movement, self-propelled motor-based biosensors have gained considerable attention. Studies have demonstrated that the continuous movement of micromotors can enhance target binding efficiency and sensitivity, allowing direct identification and isolation of different biological targets. The significantly improved analyte–receptor interactions can also be obtained through the increased fluid transport associated with propelled motions of micromotors. Through the integration of light-emitting fluorophores, self-propelled motors can continuously monitor and reflect the status of an inhomogeneous biological microenvironment.…”
mentioning
confidence: 99%